Efficacy of the benznidazole+posaconazole combination therapy in parasitemia reduction: An experimental murine model of acute chagas (2020)
Introduction: Benznidazole (BZL) and Nifurtimox (NFX) are the pharmacological treatment for acute phase Chagas Disease (CD); however, therapy resistance and residual mortality development remain important unresolved issues. Posaconazole (POS) has shown a trypanocidal effect in vivo and in vitro. Thus, this study aimed at comparing the T. Cruzi parasitic load-reducing effect of the combination of BZL+POS against that of monotherapy with either, during acute phase CD, in an experimental murine model. Methods: Nineteen Wistar rats were randomly allocated to four groups and inoculated with the trypomastigotes of T. cruzi strain´s JChVcl1. The rats were administered anti-parasites from day 20-29 post-infection. The Pizzi and Brener method was used for parasitemia measurement. Longitudinal data analysis for the continuous outcome of repeated measures was performed using parasitemia as the outcome measured at days 20, 22, 24, 27, and 29 post-infection. Results: All four groups had similar parasitic loads (p=0.143) prior to therapy initiation. Among the three treatment groups, the BZL+POS (n=5) group showed the highest mean parasitic load reduction (p=0.000) compared with the control group. Likewise, the BZL+POS group rats showed an earlier therapeutic effect and were the only ones without parasites in their myocardial samples. Conclusions: Treatment of acute phase CD with BZL+POS was more efficacious at parasitemia and myocardial injury reduction, compared with monotherapy with either. © 2020, Sociedade Brasileira de Medicina Tropical. All rights reserved.